PENGARUH KUALITAS SUMBER DAYA MANUSIA, LINGKUNGAN KERJA DAN PENEMPATAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI KPP MADYA DUA JAKARTA SELATAN II - Perdana, Dicky Arisandi; Purwanto, Purwanto; Rahayu, Sri (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effects of human resource quality, work environment, and job placement on employee work effectiveness at KPP Madya Dua Jakarta Selatan II, both partially and simultaneously. This research employs a quantitative approach with a causal associative design. The population consists of all 134 employees of KPP Madya Dua Jakarta Selatan II, and a census method is used as the sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that human resource quality, work environment, and job placement each have a positive and significant effect on employee work effectiveness. Job placement is identified as the most dominant factor influencing work effectiveness. Simultaneously, the three independent variables significantly affect employee work effectiveness, with a coefficient of determination of 78.0%, indicating that most of the variation in employee work effectiveness is explained by the research model. These findings suggest that improving employee work effectiveness requires not only enhancing individual competencies but also creating a supportive work environment and implementing appropriate job placement policies. The results are expected to provide practical insights for public sector organizations in developing more effective and integrated human resource management strategies.